Post-9/11 Latino Veteran Mental Health Service Utilization. (2nd October 2019) - Pittman, James O. E.; Baer, Judith; Everett, Joyce; Dozier, Mary E.; Almklov, Erin; Afari, Niloofar
Abstract: Previous research has identified disparities in mental health service utilization between Latinos and non-Latino Whites. This study aimed to examine patterns of mental health service utilization between Latino and non-Latino White post-9/11 war veterans ( N  = 740) enrolling for healthcare at the Veteran Affairs San Diego Healthcare System and to identify significant predictors of service utilization in Latino veterans. Predisposing, enabling, and need factors from the Behavioral Model for Health Service Utilization (BMHSU) were tested as predictors of mental health utilization. No significant differences in BMHSU factors or health service utilization emerged between Latino and non-Latino White veterans, suggesting military service may mute differences seen in civilian samples. In addition, none of the predisposing or enabling BMHSU variables significantly contributed to predict mental health utilization in Latino veterans. However, certain need variables (i.e., depression, traumatic brain injury, and pain) predicted attending one or more mental health appointments for Latino veterans. These findings reinforce the importance of assessing these particular need factors in post-9/11 Latino veterans as they have implications for treatment utilization. Furthermore, these findings suggest there may be a need to develop a model that better understands health service utilization in Latino veterans by considering the joint influence of their military identity and ethnic identity.